Psychological description at depression in combat sports - on the example of male judo - Marta Wojdat; Patrycja Janowska; Małgorzata Pujszo; Robert Stępniak; Beata Wolska (Kazimierz Wielki University, 2017)
The aim of the study was to describe the level of depression in judo practitioners - (professional and recreational)  and to find possible associations between depression and sports careers and the social functioning of this group of athletes. Studies have shown a significantly lower level of depression in the judo group, and the dependence of this phenomenon with social functioning, and a lack of association depression with quality of athletic career.